2011
DOI: 10.1002/j.0022-0337.2011.75.4.tb05074.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Business Skill Development by Graduates of the University of Michigan Dental School

Abstract: Many graduating dentists leave dental school feeling that they are not prepared to start and run a dental practice. The aim of this pilot study was to explore the knowledge and perceptions dental graduates have in the area of practice management. A twenty-item survey was mailed in the fall of 2008 to nearly half of the University of Michigan dental school alumni who had graduated between the years of 1997 and 2007. Respondents were asked about their demographics, practice characteristics, and perceptions of kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…Further, a literature review of previous studies was conducted to evaluate different topics related to practice management course. [ 6 7 8 9 10 11 12 14 15 18 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a literature review of previous studies was conducted to evaluate different topics related to practice management course. [ 6 7 8 9 10 11 12 14 15 18 ]…”
Section: Methodsmentioning
confidence: 99%
“…They improved these skills over the years during dental practice, hence stressing the need to improve such deficiencies in dental curriculum. [ 9 ] In France, undergraduate students pointed out time management and handling of administrative tasks as the main challenges at the start of their career. [ 10 ] More than half of dentists in the Netherland reported that they were not prepared for the management of dental staff, the organization of practice, legal aspects of dentistry, and matters related to dental insurance.…”
Section: Introductionmentioning
confidence: 99%
“…Although these subjects have been specifically designed for the development of A&M competencies, they do not seem to be sufficient to provide the necessary autonomy to the future dental professional, particularly taking into consideration the amplitude and depth of knowledge required to face the contemporary work market 5 . This is a reality observed not only in the dental course in question, but also in other dental graduation courses in both this country and abroad 3,4,14,15 .…”
Section: Discussionmentioning
confidence: 82%
“…Possibly, some students did not see the relevance of their education in management practice during their years at college because they are focused on acquiring the necessary technical skills to practice the profession 17 . Even though some aspects of management practice are provided by the institution during their clinical education, only when they enter the work market they begin to understand that there are other areas of their practice that also require development 3 . Part of the poor interest in A&M contents in the dental course was attributed to the fact that teachers were dentists rather than accountants or administrators.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, dental residents identified three critical areas of training for practice preparation: management, multidisciplinary coordination, and total quality management 27 . In Barber et al's survey, the majority of one dental school's alumni supported the need for interventions to increase graduating students’ knowledge and application of PM 28 . A report published in 2010 noted that recent graduates of one school assessed themselves best at integrity and worst at managing conflict 29 …”
mentioning
confidence: 99%